2017
DOI: 10.14814/phy2.13091
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent and graded exercise effects on NK cell degranulation markers LAMP‐1/LAMP‐2 and CD8+CD38+ in chronic fatigue syndrome/myalgic encephalomyelitis

Abstract: There is substantial evidence of immune system dysfunction in chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) but little is understood of exercise training effects on lymphocyte function in this illness. This study investigated whether graded and intermittent exercise improved CD8+ lymphocyte activation and natural killer cell degranulation markers compared to no exercise. Twenty‐four chronic fatigue syndrome (CFS) patients (50.2 ± 10 year) were randomized to graded exercise (GE), intermittent exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Furthermore, physical activity is essential for preventing physical and emotional disorders and maintaining a better quality of life in individuals living with HIV/AIDS (Oliveira et al, 2020) Chronic inflammation, swelling, and pain in skeletal muscles lead to chronic fatigue (Brenu et al, 2013). Studies employing graded and intermittent exercise interventions on cytotoxic cells have reported that NK cells are mobilized similarly in healthy women, suggesting that intermittent exercise may benefit the maintenance of NK cell function (Broadbent & Coutts, 2017). Broadbent and Coutts (2017) demonstrated that after 12 weeks of graded and intermittent exercise, the number and percentage of degranulated NK cells increased.…”
Section: Sporadic Inclusion Body Myositis Patients (62-73 Years)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, physical activity is essential for preventing physical and emotional disorders and maintaining a better quality of life in individuals living with HIV/AIDS (Oliveira et al, 2020) Chronic inflammation, swelling, and pain in skeletal muscles lead to chronic fatigue (Brenu et al, 2013). Studies employing graded and intermittent exercise interventions on cytotoxic cells have reported that NK cells are mobilized similarly in healthy women, suggesting that intermittent exercise may benefit the maintenance of NK cell function (Broadbent & Coutts, 2017). Broadbent and Coutts (2017) demonstrated that after 12 weeks of graded and intermittent exercise, the number and percentage of degranulated NK cells increased.…”
Section: Sporadic Inclusion Body Myositis Patients (62-73 Years)mentioning
confidence: 99%
“…Studies employing graded and intermittent exercise interventions on cytotoxic cells have reported that NK cells are mobilized similarly in healthy women, suggesting that intermittent exercise may benefit the maintenance of NK cell function (Broadbent & Coutts, 2017). Broadbent and Coutts (2017) demonstrated that after 12 weeks of graded and intermittent exercise, the number and percentage of degranulated NK cells increased. Therefore, the NK cells may be more sensitive to the increased catecholamine levels during exercise.…”
Section: Sporadic Inclusion Body Myositis Patients (62-73 Years)mentioning
confidence: 99%